Proses Produksi Program Siaran “Get In The Moz“Di 90.8 FM OZ Radio Jakarta - Ayu Putri Aryani; R. Hiru Muhammad (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2023)
Radio is still one of the mass communication media that still exists in society today. Even though many other media have emerged that provide broadcasts other than audio, radio is still in demand by many fans. This research focuses on the Production Process of the Get In The Moz Program on 90.8 FM OZ Radio Jakarta. The aim of this research is to determine the production process of the Get In The Moz broadcast program on 90.8 FM OZ Radio Jakarta starting from pre-production, production, post-production, supporting factors and inhibiting factors in the production process of the Get In The Moz broadcast program on 90.8 FM OZ Radio Jakarta. The research method used is descriptive qualitative with data collection techniques, namely observation, interviews and documentation. The informants in this research were two people plus documents issued by OZ Radio Jakarta and observations in the field. From the results of this research, it is concluded that the Production Process for the Get In The Moz Broadcast Program on 90.8 FM OZ Radio Jakarta has gone through several processes so that it can be heard by the entire audience in accordance with the SOP (Standard Operational Procedure). So as to produce a high-quality Get In The Moz program even though it still faces a number of obstacles or inhibiting factors in the production process.